Making Magic in Elizabethan England : Two Early Modern Vernacular Books of Magic - Klaassen, Frank F. (Book collections on Project MUSE., 2019)
"Examines two anonymous manuscripts of magic produced in Elizabethan England: the Antiphoner Notebook and the Boxgrove Manual. Explores how scribes assembled these texts within wider cultural developments surrounding early modern forms of magic"--Provided by publisher.